Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Maslah Matematis Siswa Sekolah Dasar - Ruroh, Imas; Mahpudin , Mahpudin (Papanda Publisher, 2023)
Education is a reference that is assessed for the progress of a nation. Good quality education is born from good quality human resources. Mathematics is one of the sciences that must exist at all levels of education. This study uses a qualitative approach and the data analysis process emphasizes more on concluding comparisons of literature reviews from several scientific journals. The results showed that the application of the Problem Based Learning model could improve students' mathematical problem solving abilities. In this case students are required to be active in groups, understand, plan to solve problems. Thus it can be concluded that the Problem Based Learning model can be an effective learning method for improving elementary school students' mathematical problem solving abilities. Education is a reference that is assessed for the progress of a nation. Good quality education is born from good quality human resources. Mathematics is one of the sciences that must exist at all levels of education. This study uses a qualitative approach and the data analysis process emphasizes more on concluding comparisons of literature reviews from several scientific journals. The results showed that the application of the Problem Based Learning model could improve students' mathematical problem solving abilities. In this case students are required to be active in groups, understand, plan to solve problems. Thus it can be concluded that the Problem Based Learning model can be an effective learning method for improving elementary school students' mathematical problem solving abilities.